Detection and genetic profiling of infectious hypodermal and haematopoietic necrosis virus (IHHNV) infections in wild berried freshwater prawn, Macrobrachium rosenbergii collected for hatchery production - Hazreen, N.M.K.; Kua, B.C.; Bhassu, S.; Othman, R.Y. (Dordrecht, Boston, Reidel., 2011)
Infectious hypodermal and haematopoietic necrosis virus (IHHNV) has been detected widely in penaeid culture facilities in Asia and the Americas. IHHNV infection on sub-adult and postlarvae of the giant freshwater prawn, Macrobrachium rosenbergii which had caused up to 80% mortalities was first reported in Southeast Taiwan in 2006. In Malaysia, although, there has been no report on IHHNV infections in M. rosenbergii, preliminary work suggests that there is an urgent need to setup a screening protocol for IHHNV for both wild and cultured populations. In this study, polymerase chain reaction based screening was carried out on 30 randomly sampled berried wild M. rosenbergii before and after spawning. All samples did not showed any sign of IHHNV infection. However, the results showed that 20% of the samples were IHHNV positive. Sequence analysis of the amplified band using NCBI-BLAST showed that the putative IHHNV sequence had 98% nucleotide sequence (388 bp) identity with the IHHNV isolate AC-05-005 non-structural protein 1 gene and seven other IHHNV strains in the data bank further affirming the suggestion on the presence of IHHNV in wild freshwater prawn populations in Malaysia.